2017
DOI: 10.1167/iovs.16-21389
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Retinal Blood Flow Measurement Using a Doppler Optical Coherence Tomography Flowmeter in Healthy Subjects

Abstract: PURPOSE. To evaluate the repeatability and reproducibility of retinal blood flow (RBF) measurements in humans by using new auto-alignment and measurement software in a commercially available Doppler optical coherence tomography (DOCT) system. METHODS.The DOCT flowmeter assessed the intrasession repeatability and the intersession and interobserver reproducibility of the RBF measurements. For intrasession repeatability, the coefficients of variation (CVs) of five repeated RBF measurements were calculated at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Retinal blood flow was measured according to a previously described method. [ 10 , 11 ] As shown in Fig 1 , Before BF imaging, a single color fundus image centered at optic disc was captured then region of interest of retinal vessel which is typically one disc diameter away from center of the optic disc was manually chosen. Scan location was also set in this procedure to make sure that it is almost perpendicular to the blood vessel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal blood flow was measured according to a previously described method. [ 10 , 11 ] As shown in Fig 1 , Before BF imaging, a single color fundus image centered at optic disc was captured then region of interest of retinal vessel which is typically one disc diameter away from center of the optic disc was manually chosen. Scan location was also set in this procedure to make sure that it is almost perpendicular to the blood vessel.…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed that the DOCT flowmeter enabled accurate and physician-friendly measurement of segmental and sum of the segmental RBFs (SRBF) without any specific skills. [ 10 , 11 ] The goal of this study was to investigate the changes in segmental RBF and SRBF during PRP in poorly controlled PDR patients using the DOCT flowmeter.…”
Section: Introductionmentioning
confidence: 99%
“…They relate the results from a specific diagnostic technique or even a specific type of a device to the established norms and pathology classifications. However, only a few papers exist reporting volumetric blood flow values measured with OCT techniques in a limited number of cases [15] [31][32][33][34][35]. Therefore, to answer the first question we have performed two tests, which do not require comparisons with established norms, yet show the reliability of the calculated volumetric flow rate values.…”
Section: Introductionmentioning
confidence: 99%
“…14 The dynamic changes around the induction of occlusion can be demonstrated using the experimental animal models of RVO induced by laser photocoagulation (PC) on a venule. 8,15,16 Recently, technological devices for measuring RBF have been developed so that it is possible to measure the absolute value of RBF by Doppler optical coherence tomography (DOCT) flowmeter 10,[17][18][19] and noninvasively evaluate the detailed microvascular formations by optical coherence tomography angiography (OCTA). 13,20 In the present study, we investigated the longitudinal changes in RBF in terms of the functional and microvascular formation changes simultaneously with the structural changes using DOCT and OCTA in a PC-induced feline RVO model.…”
mentioning
confidence: 99%